102k views
4 votes
I need help with these questions if you don’t mind

I need help with these questions if you don’t mind-example-1
User VinothRaja
by
5.5k points

1 Answer

3 votes

3. If EG is equal to 71, we can write the following equation

EF + FG = 71

Where EF = 8x - 17 and FG = 5x - 3

Replacing, we get:

EF + FG = 71

(8x - 17) + (5x - 3) = 71

8x - 17 + 5x - 3 = 71

Solving for x, we get:

8x - 17 + 5x - 3 = 71

13x - 20 = 71

13x - 20 + 20 = 71 + 20

13x = 91

Dividing in both sides by 13, we get:


\begin{gathered} (13x)/(13)=(91)/(13) \\ x=7 \end{gathered}

Answer: x = 7

User Riyas Ac
by
5.5k points